2021
DOI: 10.21037/atm-21-2114
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs as potential regulators in bone remodeling: a narrative review

Abstract: In this review, we focus on the recent progress of circular ribonucleic acids (circRNAs)-related molecular mechanisms in the processes of osteogenesis and osteoclastogenesis, and explore their roles in the development of bone-remodeling disorders.Background: The well-coupled bone-formation and bone-resorption processes are vital in bone remodeling. Once the balance is disrupted, bone-remodeling disorders (e.g., osteoporosis and osteopetrosis) occur, severely affecting patients' quality of life. CircRNAs, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 113 publications
(138 reference statements)
0
13
0
Order By: Relevance
“…By modulating cell metabolism ( 15 ), cell proliferation ( 16 ), cell apoptosis ( 17 ), and other functions ( 18 ), circRNAs are involved in the incidence and development of some diseases, such as cancers ( 19 ), neurological diseases ( 20 ), heart diseases ( 21 ), and endocrine diseases ( 22 ), and circRNAs can function as therapeutic targets and biomarkers. Meanwhile, emerging researches indicated that circRNAs are also potential regulators of osteoporosis ( 23 ). For example, some studies revealed that hsa_Circ_0001275, hsa_circ_0002060, and hsa_circ_0006859 are recognized as potential novel diagnostic biomarkers of osteoporosis ( 2 , 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…By modulating cell metabolism ( 15 ), cell proliferation ( 16 ), cell apoptosis ( 17 ), and other functions ( 18 ), circRNAs are involved in the incidence and development of some diseases, such as cancers ( 19 ), neurological diseases ( 20 ), heart diseases ( 21 ), and endocrine diseases ( 22 ), and circRNAs can function as therapeutic targets and biomarkers. Meanwhile, emerging researches indicated that circRNAs are also potential regulators of osteoporosis ( 23 ). For example, some studies revealed that hsa_Circ_0001275, hsa_circ_0002060, and hsa_circ_0006859 are recognized as potential novel diagnostic biomarkers of osteoporosis ( 2 , 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a class of covalently closed RNAs widely expressed in eukaryotic cells 12–14 . They are usually derived from reverse splicing of transcripts by a non‐classical splicing mechanism 15–17 .…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a class of covalently closed RNAs widely expressed in eukaryotic cells. 12 , 13 , 14 They are usually derived from reverse splicing of transcripts by a non‐classical splicing mechanism. 15 , 16 , 17 Although the majority of circRNAs do not code for proteins, some circRNAs were reported to be translated into protein products in cancer cells with unclear functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…circRNA can lift the repressive effect of miR-NAs on their target genes through miRNA sponge action [7,8]. circRNAs are irregularly expressed in countless tumors and are involved in regulating NF-κB, PI3K/AKT, TGF-β, and JAK-STAT signaling pathways [9][10][11][12], thereby affecting tumor development. It was shown that circVANGL1 in NSCLC inhibits miR-195 by adsorbing miR-195 and thus negatively regulates downstream genes [13].…”
Section: Introductionmentioning
confidence: 99%